PERCEIVED SOCIAL MEDIA MARKETING ACTIVITIES AND CONSUMER-BASED BRAND EQUITY - Rega Hardiana Aditia; Adi Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research's objective is to look into how consumers' social media marketing activities affect consumer-based brand equity by using brand experience as a mediating factor and co-creation activity as a moderator variable. The Stimulus–Organism–Response (SOR) theory, which holds that The internal state of a person is impacted by outside stimuli prior to conduct, serves as the foundation for this study. In this study, consumer-based brand equity is the reaction, brand experience is the organism, and social media marketing activities are the stimulus. A quantitative approach was implemented by surveying 100 active TikTok users who had seen and utilized Scarlett products. The Statistical Package for Social Sciences (SPSS) was used to analyze the data using path analysis, the Sobel mediation test, and Moderated Regression Analysis (MRA) To assess the measurement model and structural model concurrently, including mediation and moderation tests. The results of the study demonstrate that consumer-based brand equity and brand experience are impacted by perceived social media marketing efforts. Additionally, The correlation between consumer-based brand equity and social media marketing actions was found to be mediated by brand experience. Additionally, co-creation behavior increases the impact of social media marketing on the brand experience. The results show that interactive marketing strategies that promote user involvement on TikTok can improve user-based brand equity and improve the brand experience. In the context of digital marketing, this work contributes theoretically to the development of the SOR model. Additionally, it provides useful guidance for businesses as they create consumer-focused social media strategy.